Environmental location factors of selected strongholds in central Western Poland: https://doi.org/10.26485/AGL/2018/107/6 - Twardy, Juliusz; Forysiak, Jacek; Rodak, Sylwia; Moździoch, Sławomir (Acta Geographica Lodziensia, 2018)
The paper presents environmental factors that influenced the location of four selected early medieval strongholds in central Western Poland. The following objects were examined: a stronghold at Bobrowniki, on the border between the Warta-Odra Pradolina and Zielona Góra Hillocks, a stronghold at Bytom Odrzański in the Odra River valley within the Głogów Pradolina, and strongholds at Solniki and Popęszyce in the Dalków Hills. Geomorphic and Quaternary research was carried out during fieldworks, while other environmental factors were analysed from literature and cartographic sources. The relief was considered the dominant factor; it was very important to provide a defensive location for the strongholds at Bobrowniki, Solniki and Popęszyce. In two cases (Solniki and Bobrowniki), finding suitable geomorphological forms, such as intervalley rims and high erosional edges, enabled the stronghold to be settled almost without building ramparts. Besides relief, hydrology was also important (the course of river channels and the distribution of wetlands and marshes at the bottom of a large river valley), which ensured the defensive location at Bytom Odrzański. Other natural factors had an ambiguous and generally smaller impact on the settlement of strongholds in the early Middle Ages in central Western Poland.